RISKS AND CONSIDERATIONS IN ORAL REHABILITATION OF ELDERLY HYPERTENSIVE PATIENTS - Gabi Topor; Iulia Alecsandra Salcianu; Alina Mihaela Calin; Nicolae Sarbu; Minodora Campanu (Banu); Olimpia Dumitriu-Buzia; Solomon Sorina; Victorita Stefanescu; Norina Consuela Forna; Iulian Catalin Bratu (Romanian Society of Oral Rehabilitation, 2024)
Oral rehabilitation of elderly hypertensive patients presents specific challenges, given the increased prevalence of systemic complications in this group. Hypertension can significantly influence dental management through drug interactions, oral side effects of antihypertensive therapies, and special needs during dental procedures. The complex and interdisciplinary approach to the management of oral rehabilitation of elderly hypertensive patients is essential to ensure safe and effective treatment. By implementing personalized assessment, intervention and education strategies, the quality of care provided to this group of patients can be significantly improved, optimizing treatment outcomes and improving their quality of life. This article reviews existing literature and explores the main risks and considerations for optimizing oral care in these patients.